EXPRESSING IMPERATIVE SENTENCES IN ENGLISH AT DIFFERENT LEVELS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the multi-faceted nature of imperative sentences in the English language, moving beyond simple grammatical structures to analyze their pragmatic functions across different social levels. The study investigates how imperatives are softened or intensified based on the relationship between the speaker and the listener, the urgency of the situation, and the social hierarchy. By examining direct commands, polite requests, and suggestive imperatives, the research highlights the importance of "face-saving" acts in English communication. The methodology includes a qualitative analysis of linguistic markers and a comparative study of formal versus informal discourse.